Ethyl p-methoxycinnamate from Kaempferia galanga inhibits angiogenesis through tyrosine kinase - Juni Ekowati; Suko Hardjono; Iwan Sahrial Hamid (Faculty of Medicine, Universitas Trisakti, 2015)
BACKGROUNDMany tumors express on their receptor tyrosine kinases vascular endothelialgrowth factor activity associated with angiogenesis. Inhibition ofangiogenesis through reduction of tyrosine kinase activity is a promisingstrategy for cancer therapy. The present study aimed to determine themechanism and potency of ethyl p-methoxycinnamate (EPMC) isolatedfrom Kaempferia galanga as angiogenesis inhibitor.METHODSA laboratory experimental study was conducted using chorio-allantoicmembranes (CAMs) of nine-day old chicken eggs induced by 60ng basicfibroblast growth factor (bFGF). Ethyl p-methoxycinnamate (EPMC) potencywas determined at dosages of 30, 60, 90 and 120 μg and compared withcelecoxib 60 μg as reference drug and one negative bFGF-induced controlgroup. Neovascularization and endothelial cell count in CAM blood vesselswere evaluated. To predict the antiangiogenic mechanism of EPMC, adocking study was performed with the Molegro Virtual Docker program ontyrosine kinase as receptor (PDB 1XKK).RESULTSAngiogenesis stimulation by bFGF was prevented significantly (p<0.05)by EPMC at dosages of 30, 60, 90 and 120 μg and this activity was dosedependent. Molecular docking showed interaction between EPMC functionalgroups and tyrosine kinase amino acids at Met766, Met793, Thr854, Thr790,Gln791 and Ala743. There was an association between EPMCantiangiogenic activity and docking study results.CONCLUSIONSEthyl p-methoxycinnamate is a potential new angiogenesis inhibitor throughinteraction with tyrosine kinase. EPMC could be a promising therapeuticagent for treatment of angiogenesis-related diseases.